Docking Studies of HIV-1 Reverse Transcriptase and HIV-1 Protease with Phytocompounds of Carissa Carandas L. - Singh, Reetika; Nath, Abhigyan; Sharma, Bechan (Journal of Clinical Research In HIV AIDS And Prevention, 2019)
Background Carissa carandas L. is a well-known wild fruit plant distributed through-out the India and also present in other countries. The fruits are rich in nutrients and minerals. A number of medicinally important phytochemicals such as carrisone, carindone, carandinol, lupeol, scopoletin, stigmasterol, β-sitosterol, myo-inositol, β-amyrin, Des-n-methylnoracronycine etc. have been reported from the extract of this plant. Being safe and cost effective molecules, the activity of phytochemicals against HIV-1 enzymes needs to be screened. Objective The aim of this study was to screen the potent phytocompound of C. carandas against human immunodeficiency virus-1 using docking method. Methods Total nine compounds viz. carandinol, caridone, carrisone, lupeol, p-coumaric acid, gallic acid, rutin, scopoletin and ursolic acid were used for in-silico study towards drug development against human immunodeficiency virus-1 reverse transcriptase (HIV-1RT; PDB ID: 1REV) and human immunodeficiency virus-1 protease (PDB ID:1EBY) using Autodock software. Results The qualitative characterization of the extracts showed the presence of a number of phytochemicals such as phenolics, flavonoids, alkaloids, terepnoids, terpenes, steroids, glycosides etc. Carandinol was observed as most effective anti-HIV-1 molecule having lowest binding energy and small inhibition coefficient. Another compound, p-coumaric acid, showed least effectiveness against human immunodeficiency virus- 1 reverse transcriptase or human immunodeficiency virus-1 protease showing highest binding energy and inhibition coefficients among all the evaluated phytocompounds. Conclusion The in-silico study demonstrated that some phytoconstituents of C. carandas exhibit potential anti-human immunodeficiency virus -1 activity and hence can be optimized to develop as a drug candidate in future.
Keywords: Carissa carandas; Phytochemicals; HIV-1RT; HIV-1protease; Anti HIV-1Drugs